A self-calibrating Hall sensor IC with direction detection. - Draxelmayr, D. (IEEE Journal of solid state circuits)
A monolithic wheel speed sensor integrated circuit based on Hall effect is presented. Speed and motion direction of magnetic encoder wheels or ferromagnetic target wheels are detected. Two specific amplitudes of the magnetic input signal are detected as well. A two-wire current output directly linked to the input signal frequency indicates speed. Direction information and detection of specific amplitudes of the magnetic input signal are encoded in its output pulsewidth. It features a strictly differential sensing principle, a new direction detection algorithm, and a dynamic self-calibrated offset compensation. The integrated circuit is manufactured in a 0.6-μm BiCMOS process, enhanced by bipolar transistors with increased breakthrough voltage.